The Impact of Firm Specific Factors on the Stock Prices: Empirical Evidence from Belgrade Stock Exchange - Milošević Avdalović, Snežana (Industrija, 2018)
This study aims to examine the impact of certain determinants of stock prices on the capital market in development, with a special focus on companies in the Financial and Insurance Activities Sector whose shares are listed on the Belgrade Stock Exchange. The study uses data from individual companies from 2008 to 2014 and employed ordinary least squares method. Generally speaking, the study found that accounting information, in particular, return on assets, book value per share, trust rate and company size measured by market capitalization, are relevant for explaining the stocks prices in Serbia. This study contributes to the current discussion of specific factors affecting the price of stocks in the emerging market with a special focus on the Belgrade Stock Exchange. Cluster analysis of companies according to key determinants of share prices suggests to investors that there is the possibility of portfolio diversification. The reliability in the study is ensured by including nearly 95% of the companies listed on the Belgrade Stock Exchange, ie shares of companies classified in K - Financial and Insurance Activities Sector on the Belgrade Stock Exchange.
Keywords: Financial performances; Financial and Insurance Activities Sector; Stock exchange; Stock price